Failure to remap visuotactile space across the midline in the split-brain. - Spence, C; Shore, D; Gazzaniga, MS; Soto-Faraco, S; Kingstone, A (2001)
We examined the effect of posture change on the representation of visuotactile space in a split-brain patient using a cross-modal congruency task. Split-brain patient J.W. made speeded elevation discrimination responses (up versus down) to a series of tactile targets presented to the index finger or thumb of his right hand. We report congruency effects elicited by irrelevant visual distractors placed either close to, or far from, the stimulated hand. These cross-modal congruency effects followed the right hand as it moved within the right hemispace, but failed to do so when the hand crossed the midline into left hemispace. These results support recent claims that interhemispheric connections are required to maintain an accurate representation of visuotactile space.